2016
DOI: 10.1007/s00395-016-0543-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding STAT3 signaling in cardiac ischemia

Abstract: Cardiovascular disease is the leading cause of death worldwide. It remains one of the greatest challenges to global health and will continue to dominate mortality trends in the future. Acute myocardial infarction results in 7.4 million deaths globally per annum. Current management strategies are centered on restoration of coronary blood flow via percutaneous coronary intervention, coronary artery bypass grafting and administration of anti-platelet agents. Such myocardial reperfusion accounts for 40-50 % of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 111 publications
1
46
0
Order By: Relevance
“…Transcription factor binding site analysis of up- and down-regulated mRNAs in our experimental MI model identified a specific enrichment pattern of several putatively important transcription factors in the heart after MI. Many of these transcription factors have been shown to play crucial roles in pathophysiology of MI [ 44 , 45 ] . Among them are the homeobox transcription factor Nkx2-5 and the zink finger transcription factors Klf4.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factor binding site analysis of up- and down-regulated mRNAs in our experimental MI model identified a specific enrichment pattern of several putatively important transcription factors in the heart after MI. Many of these transcription factors have been shown to play crucial roles in pathophysiology of MI [ 44 , 45 ] . Among them are the homeobox transcription factor Nkx2-5 and the zink finger transcription factors Klf4.…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin is another extracellular matrix, and the fibronectin extra domain-A (ED-A) is crucial in myofibrosis [ 9 ]. STAT3 has been documented to promote the transcription of target genes, including CCN2 [ 10 ] and other genes [ 11 ], via direct interactions with consensus sites in the promoter regions. Recently, drug-induced peroxisome proliferator-activated receptor δ (PPARδ) activation has been shown to attenuate STAT3 expression for the improvement of DCM in rats [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 is important for cardiomyocyte function via modulation of mitochondrial and transcriptional responses, and, beyond that role, it also modulates the cardiac microenvironment and communicates with cardiac fibroblasts [17]. In addition, the latest study from our group has demonstrated that phosphorylation of STAT3 can activate Akt and that both play critical roles in the activation of endothelial nitric oxide synthase (eNOS) and the subsequent attenuation of myocardial IR injury [18].…”
Section: Introductionmentioning
confidence: 99%